Characteristics of Biomass Briquettes in term of Variations in Raw Materials and Different Percentages of Adhesive - AK, Agnesia Arista Wijaya; Yulianti, Ni Luh; Gunadnya, Ida Bagus Putu (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
This study aims to determine the characteristics and effects of the types of raw materials and the percentage of different adhesives on the quality of the resulting briquettes and determine which treatment gives the best results for the characteristics of the resulting briquettes. This study used a factorial randomized block design (RBD) using 2 factors and 3 replications. The first factor (A) is the type of raw material which consists of 3 levels, namely tabah bamboo (A1), rice husk (A2) and a mixture of tabah bamboo and rice husk (A3). The second factor (B) is the percentage of adhesive which consists of 3 levels, namely the percentage of 10%, (B1) 15% (B2) and 20% (B3). The research parameters observed were moisture content, ash content, volatile substance content and combustion rate. All treatments were repeated 3 times in order to obtain 27 experimental units. The data obtained were analyzed by means of variance and if there was a significant treatment effect, it was continued with the Duncan Multiple test (DMRT). Based on the results of the study, it is known that the treatment interaction has a significant effect on the parameters of moisture content, ash content, volatile substance content and combustion rate. Furthermore, the water content obtained ranged from 2.30% wt - 4.78%, bb ash content 5.88% - 34.85%, evaporating substance content 31.30% - 51.59% and combustion rate 73.20 gr / minute - 106.00 gr / minute. The best quality of briquettes was obtained in A2B3 treatment (80 grams of rice husk 20 grams of adhesive) where the resulting moisture content was 2.30% BW, 32.29% ash content, 32.01% volatile substance content and 92.60 gr burning rate /minute.